“PATERAS, EMBARAZADAS Y PROSTITUCIÓN”: REPRESENTACIONES Y DISCURSOS SOBRE LA MUJER INMIGRANTE EN LA TELEVISIÓN ESPAÑOLA - Antonia OLMOS ALCARAZ (Fonseca, Journal of Communication, 2023)
This article analyses the image that Andalusian public television offers of immigrant women in Spain, from the observation of a news programme -Canal Sur Noticias- inside the research project ‘Speeches of foreigners in media in Andalusia: the visual and discursive construction the new Andalusia’ (Project of Excellence Andalusia. TIC-6517). To do this we have reviewed the main topics associated with the women, noting with which issues they are related.